2013
DOI: 10.1353/csd.2013.0022
|View full text |Cite
|
Sign up to set email alerts
|

The Fronts Students Use: Facebook and the Standardization of Self-Presentations

Abstract: This empirical study explored the impression management techniques and standardized performances college students use on their Facebook profiles to ensure their peers believe they are fully participating in the undergraduate experience. Employing an ethnographic research design and data collected using participant-observation and interview methods, I considered the texts and images that appear repeatedly on Facebook profiles from a dramaturgical framework. I found that participants in this study identified at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Birnbaum (2013) notes that undergraduates consciously think about the impressions they want to make to peers on media sites like Facebook (Martinez-Alemán and Wartman, 2008); therefore, they spend a lot of time managing their profiles to provide the impression of themselves that they desire (Reich, 2010). This impression management is directly relevant to depictions of college drinking on Facebook.…”
Section: Jssmentioning
confidence: 99%
See 3 more Smart Citations
“…Birnbaum (2013) notes that undergraduates consciously think about the impressions they want to make to peers on media sites like Facebook (Martinez-Alemán and Wartman, 2008); therefore, they spend a lot of time managing their profiles to provide the impression of themselves that they desire (Reich, 2010). This impression management is directly relevant to depictions of college drinking on Facebook.…”
Section: Jssmentioning
confidence: 99%
“…The same study looked at what people posted on each other's profiles and found that 50% of the posts involved partying. Hence, Facebook profiles would contain posts and images that students intentionally believe are most likely to convince their audience, especially their peeers, that they are fitting into the expectations of college life (e.g., drinking), even if the discloser does not actually participate in these behaviors as much as the profile would suggest (Birnbaum, 2013). Furthermore, not only do college students need to make it look like they eagerly and willingly participate in this college partying culture, they need to do it in an "extreme" way that is viewed by this generation as "cool"; and, documenting this behavior on Facebook is a means of proof.…”
Section: Jssmentioning
confidence: 99%
See 2 more Smart Citations
“…Teenagers and college students are socialized regarding adult emotional expression from a variety of sources -family, friends, and social media to name a few. Peer socialization is especially salient at this time (Erikson, 1968;Williams & Merten, 2009;Brechwald & Prinstein, 2011) and young people's involvement in social media sites is now well documented (Bazarova, 2012;Birnbaum, 2013; Duggan, Ellison, Lampe, Lenhart, & Madden, 2015). For example, according to Duggan and colleagues (2015), almost 90% of teens and young adults in the United States use Facebook; and some researchers claim that the average number of Facebook friends for college students is approximately 650 people (www.statista.com, 2014).…”
Section: Emotion Socializationmentioning
confidence: 99%